Publisher Correction: Time dependent decomposition of ammonia borane for the controlled production of 2D hexagonal boron nitride. Issue 1 (December 2017) - Babenko, Vitaliy; Lane, George; Koos, Antal; Murdock, Adrian; So, Karwei; Britton, Jude; Meysami, Seyyed; Moffat, Jonathan; Grobert, Nicole
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.